Snow cover determines the ecology and biogeography of spiders (Araneae) in alpine tundra ecosystems - Hein, Nils; Feilhauer, Hannes; Finch, Oliver-D.; Schmidtlein, Sebastian; Löffler, Jörg (ERDKUNDE, 2014)
This study addresses the spatial distribution of spiders (Araneae) in relation to their environment along multiple ecological and biogeographical gradients. Two study regions representing considerable variation in the alpine climate were sampled for epigeal spiders using pitfall traps: one in the oceanic region and one in the continental region of Norway. We aimed to identify the driving forces for spider species annidation in an alpine tundra ecosystem using a multi-scale approach. During the snow-free season in 2009, we sampled 6,628 adult specimens at 73 sampling locations. These data and additional information from previous studies on spider habitat preferences were used to examine the features of the species’ spatial distribution. We analysed our data set using ordination space partitioning (Isopam), which relies on hierarchical partitioning of the ordination space. This method is based on a hierarchical classification of the sampling locations according to their species composition and results in classes that can be distinguished by indicator species. The aggregated classes and their spatial patterns could be linked to snow cover. Local climatic conditions had a stronger influence on spider biogeography than did broad-scale climatic conditions. We identified various indicator species for typical alpine tundra habitats that could be described as either ‘chionophobous’ or ‘chionophilous’, depending on the topography-related snow cover at the sites where they occurred. Through this multi-scale approach, this study is the first to demonstrate the importance of snow-cover patterns on the ecology and biogeography of spiders in alpine tundra ecosystems.